Asciminib maintains antibody-dependent cellular cytotoxicity against leukemic blasts - Holzmayer, Samuel J.; Kauer, Joseph; Mauermann, Jonas; Roider, Tobias; Märklin, Melanie (Cancers, 2024)
B cell acute lymphoblastic leukemia (B-ALL) is characterized by an accumulation of malignant precursor cells. Treatment consists of multiagent chemotherapy followed by allogeneic stem cell transplantation in high-risk patients. In addition, patients bearing the BCR-ABL1 fusion gene receive concomitant tyrosine kinase inhibitor (TKI) therapy. On the other hand, monoclonal antibody therapy is increasingly used in both clinical trials and real-world settings. The introduction of rituximab has improved the outcomes in CD20 positive cases. Other monoclonal antibodies, such as tafasitamab (anti-CD19), obinutuzumab (anti-CD20) and epratuzumab (anti-CD22) have been tested in trials (NCT05366218, NCT04920968, NCT00098839). The efficacy of monoclonal antibodies is based, at least in part, on their ability to induce antibody-dependent cellular cytotoxicity (ADCC). Combination treatments, e.g., chemotherapy and TKI, should therefore be screened for potential interference with ADCC. Here, we report on in vitro data using BCR-ABL1 positive and negative B-ALL cell lines treated with rituximab and TKI. NK cell activation, proliferation, degranulation, cytokine release and tumor cell lysis were analyzed. In contrast to ATP site inhibitors such as dasatinib and ponatinib, the novel first-in-class selective allosteric ABL myristoyl pocket (STAMP) inhibitor asciminib did not significantly impact ADCC in our settings. Our results suggest that asciminib should be considered in clinical trials.
Gesehen am 23.09.2024